Negotiated Sharing of Pandemic Data, Models, and Resources. Issue 4 (1st October 2020) - Cutcher‐Gershenfeld, Joel; Baker, Karen S.; Berente, Nicholas; Berkman, Paul Arthur; Canavan, Pat; Feltus, F. Alex; Garmulewicz, Alysia; Hutchins, Ron; King, John Leslie; Kirkpatrick, Christine; Lenhardt, Chris; Lewis, Spencer; et al.
Abstract : Urgent responses to the COVID‐19 pandemic depend on increased collaboration and sharing of data, models, and resources among scientists and researchers. In many scientific fields and disciplines, institutional norms treat data, models, and resources as proprietary, emphasizing competition among scientists and researchers locally and internationally. Concurrently, long‐standing norms of open data and collaboration exist in some scientific fields and have accelerated within the last two decades. In both cases—where the institutional arrangements are ready to accelerate for the needed collaboration in a pandemic and where they run counter to what is needed—the rules of the game are "on the table" for institutional‐level renegotiation. These challenges to the negotiated order in science are important, difficult to study, and highly consequential. The COVID‐19 pandemic offers something of a natural experiment to study these dynamics. Preliminary findings highlight: the chilling effect of politics where open sharing could be expected to accelerate; the surprisingly conservative nature of contests and prizes; open questions around whether collaboration will persist following an inflection point in the pandemic; and the strong potential for launching and sustaining pre‐competitive initiatives.